Risk factors of maternal mortality due to complications in pregnancy, delivery and postpartum in Bima Regency 2011–2012 - Sri Juharni; I Ketut Tangking Widarsa; Dewa Nyoman Wirawan (Universitas Udayana, 2013)
The maternal mortality rate (MMR) in West Nusa Tenggara Province in 2010 is about 350/100,000 live births. This figure is higher than national and other provincial figures. Bima that constitutes a regency of West Nusa Tenggara Province has high maternal mortality cases for period of 2011-2012, namely 20 cases. The Ministry of Health classified 3 factors that affect maternal mortality, namely: medical, non-medical and health service factors. The study was aimed at finding out the risk factors that affect maternal mortality. This study is a case control study with the total samples of 20 cases and 60 controls. The data were collected through interviews by using the questionnaires. The collected data were then cross-checked with the registers existing at midwives, health record cards of pregnant women and verbal autopsy documents. The univariate, bivariate and multivariate analyses were done. Bivariate analysis was using chi square test and multivariate analysis was using logistic regression. The study revealed that factors which increase the maternal mortality rate are the level of Hb<10 gr% (OR=15.19; 95%CI: 3.25–70.97), delayed decision-making (OR=9.28; 95%CI: 2.15–84.80) and delayed medical treatment at referral facilities (OR=13.16; 95%CI: 2.28–104.86). As conclusion, the most contributing factor to maternal mortality is the level of Hb<10 gr%. The efforts to reduce mortality rate should be conducted including increasing Hb level of pregnant women, improving basic obstetric emergency handlings at community health centres for midwives/medical doctors and to improve better referral systems.